Riding the rate wave: Interest rate and run risks in euro area banks during the 2022-2023 monetary cycle - Jonathan Rice; Giulia Maria Guerrini (European Central Bank (ECB), 2025)
This paper examines how the ECB's 2022-2023 interest-rate hikes affected euro-area banks' economic net worth and vulnerability to deposit runs. Drawing on granular, confidential data for 139 banks, we estimate each bank's economic net worth and find that unrealised losses on loans and bonds averaged around 30 per cent of equity. By September 2023, however, roughly half of these losses had been offset by gains from the deposit franchise and interest-rate swaps. We develop a theoretical framework linking banks' economic net worth and deposit-rate setting to depositor behaviour and run incentives. Further results indicate that banks with larger unrealised losses raised their deposit rates by less - a pattern we interpret as banks leveraging a more valuable deposit franchise to fund longer-duration assets. Although euro-area banks as a whole avoided widespread runs, several institutions nonetheless carried substantial mark-to-market losses, suggesting latent fragilities.
Keywords: G21; E43; E58; G28; 330; Interest rate risk; bank runs; monetary policy; asset valuations; euro area banking system